The ocean remains intact - Choo, Rachel Sweet Ching (Nanyang Technological University, 2022)
The Ocean Remains Intact grapples with the artist’s fears and uncertainties towards life after experiencing a close call with death at the age of nineteen. Diagnosed with various autoimmune disorders, she’s forced to constantly walk on eggshells, unsure of when her body will fail on her next. This project makes use of the photo medium to reveal the unseen struggles and frustrations of the artist towards the irregularity of her life, as well as a deeper desire to take full control over it.